Development and Preliminary Usability Evaluation of a Somatosensory Square Dance System for Older Chinese Persons: Mixed Methods Study - Yu, Chin-Wen; Rau, Pei-Luen Patrick; Liu, Xueqian (JMIR Publications, 2020)
BackgroundChinese square dancing, known as guangchang wu in Chinese, is a well-known public fitness activity that provides an entertaining way for older Chinese women to improve their flexibility, lower extremity strength, overall coordination, and balance. However, injuries, noise conflicts, and lack of space are challenging aspects of this activity. Somatosensory games (SG) are an increasingly popular physical fitness approach to enhance the selective attention of older persons with indoor engagement and exercises. ObjectiveThe objectives of this study were to develop a newly designed somatosensory square dance system for older Chinese people and to evaluate its usability. MethodsThis is a mixed methods study. The newly designed somatosensory square dance system is a somatic training tool that provides adequate Chinese square dance fitness training based on Laban Movement Analysis (LMA) and design guidelines established in a previous stage. The usability evaluation involved a questionnaire and interviews. Twelve participants were interviewed before and after experiencing the 15-minute dancing and learning process within the program. In addition, participants scored their experience satisfaction in psychological, physiological, and relaxation sections on a scale of 1 to 5 using a questionnaire. Qualitative content analysis and quantitative analysis of the satisfaction scores supported understanding of usability problems. ResultsBased on the interview results, 6/12 (50%) of the participants thought the system could help them correct their dancing movements indoors without being affected by poor outdoor weather. Among the participants, 3/12 (25%) indicated that this indoor system could enable them to enjoy fitness activities in a private space. Moreover, 3/12 participants (25%) stated that this system could promote family relationships by providing easy dancing movements. All participants were highly satisfied with the relaxation aspect of the system (4.45/5). The participants were all psychologically satisfied and interested in the novel features of the system, with an average score of 4.16/5. Physiologically, participants affirmed that the system could help them maintain good health (4.91/5). ConclusionsThe results of this study suggest that the somatosensory square dance system can be used as an indoor fitness tool to improve older Chinese square dancers' health conditions with reasonable dance training. Noise and space conflicts can be addressed. The Laban Elated Square Dance system, which was modified by therapists based on LMA and square dance design guidelines, was highly approved by dancers because it decreased the possibility of injuries, falls, and joint damage by considering the physical and psychological difficulties of older persons. Different features will be considered in the next stage, such as greater selection of exercises and difficulty level settings. Users' social needs will also be explored in subsequent stages.